WORKERS JOB SATISFACTION IN TEXTILE FACTORY: BIBLIOMETRIC ANALYSIS - Sindhu Priyo W.; M. Saad Salahudin; Atika Sanjani Ramadina (Transpublika Publisher, 2024)
Textile industry represents one of the most competitive industries. Consequently, the management tend to create pressures to their workers to pace with the high productivity level. This constant pressure given to the workers may possibly affect their job satisfaction. Hence, this study focuses on the bibliometric analysis in mapping the trend, conceptual structure, and characteristic of job satisfaction of textile factory workers. The data collection process results in 147 papers out of the total of 241 extracted papers. According to the bibliometric analysis, research in this field is mainly led by the USA and France. The co-occurrence analysis shows Four major theme: Study on job satisfaction, worker’s health assessment, cultural influence on textile factory workers, and review on absenteeism. The results indicate that workers were more concerned about the security of their current position rather than overall employment security, and this factor affected their job satisfaction and well-being.